Cover Picture: En Route to New Therapeutic Options for Iron Overload Diseases: Matriptase‐2 as a Target for Kunitz‐Type Inhibitors (ChemBioChem 7/2016). (1st April 2016) - Beckmann, Anna‐Madeleine; Maurer, Eva; Lülsdorff, Verena; Wilms, Annika; Furtmann, Norbert; Bajorath, Jürgen; Gütschow, Michael; Stirnberg, Marit
Abstract : The cover picture shows the proposed regulatory mechanism of the type II transmembrane serine protease matriptase‐2 predominantly expressed at the surface of hepatocytes. Human matriptase‐2 is a critical stimulator of iron absorption by negatively regulating hepcidin, the key hormone of iron homeostasis that controls dietary iron uptake and the release of iron from macrophages and hepatocytes. This involves the BMP/SMAD signalling pathway through cleavage of the BMP co‐receptor hemojuvelin (HJV). As a negative regulator of hepcidin, matriptase‐2 is an attractive target for correcting iron overload. The Kunitz‐type inhibitors hepatocyte growth factor activator inhibitor 1 (HAI‐1) and 2 (HAI‐2) were charaterised as powerful inhibitors of matriptase‐2. Different assays were applied to determine the inhibition constants and to evaluate the downstream consequences in human liver cells; they demonstrated that HAI‐2, in particular, represents a scaffold for the design of potent matriptase‐2 inhibitors. The binding mode of the matriptase‐2‐HAI‐2 complex suggested by molecular modelling is illustrated. More information can be found in the full paper by M. Stirnberg et al. onpage 595 in Issue 7, 2016 (DOI:10.1002/cbic.201500651 ).